Mobile Devices of Resistance - Jungnickel, Kat (meson press, 2017)
While middle- and upper-class Victorians were quick to embrace the bicycle, cycling proved materially and ideologically challenging for women. Conventional women’s fashions were vastly inappropriate for cycling: materials caught in wheels and tangled in pedals. Yet, looking too much like a cyclist in some contexts challenged established gender norms about how and in what ways women should move in and through public, to the point where cycling women suffered verbal and sometimes even physical abuse. This essay explores how some Victorians responded to challenges to women’s freedom of movement by patenting “convertible” cycle wear. These material interventions enabled women to resist social and physical limitations on their mobile bodies and identities. Drawing on feminist science and technology studies, archival research, and patents, this essay critically explores these unique garments as heterogeneous human and non-human devices and discusses how they operated as creative socio-technical mobile devices of resistance.
Victorian Inventors, Women Cyclists, and Convertible Cycle Wear
Keywords: Emanzipation; Technik; Mobilität; Diskriminierung; Normen; Sexismus; Widerstand; Mode; Gender; 608 Erfindungen, Patente; Fahrrad